BEYOND EPISTEMOLOGICAL RELIGIOUS TRUTH A REFLECTION OF THE OTHER OUTSIDE âTRUE-FALSEâ CATEGORY - Purwadi, Yohanes Slamet (Sekolah Pascasarjana UGM, 2012)
The aim of this paper is to investigate the problematic and dynamic of âreligious truthâ, put into the context of religious freedom in todayâs Indonesia. Generally speaking, the dominant discourse of religious truth in Indonesia is heavily determined by epistemological knowledge and understanding. In everyday language, through which this knowledge is produced and distributed, some epistemological categories, such as âdeviant-believerâ, âtrue- falseâ, and even âblasphemyâ- are commonly applied. Here, in the problem lies these categorizations might open up possibility for the ïxation of âtruthâ, which in turn, inclines to subordinate what generically refer to as âthe otherâSeekingÂ Â Â anÂ Â Â alternative,Â Â Â thisÂ Â Â paperÂ Â Â attemptsto develop more favorable and inclusive religious understanding, which indebted to the mode of existential religious understanding including linguistic model of translation. Employing Ricouerianâs hermeneutics, this mode of existential understanding offers valuable critique to the monopoly and orthodoxy of religious truth. Moving further, it promotes the others as an interpretative horizon and a âcircling wayâ, through which we enrich our religious understanding, as well as self-understanding.